HEAT TREATMENT REGIME OF THE INITIAL ALUMINUM HYDROXIDE TO FORM MODIFICATIONS OF Γ AND Α-AL 2 O 3 - Safarova Ruxshona Ulug‘bek qizi; Bekov Ulug’bek Safarovich (TADQIQOTLAR, 2025)
Abstract:  To  obtain  high-quality  ceramics,  it  is  necessary  to  grind  the  raw material and obtain a fine-dispersed structure. This problem was solved by converting aluminum waste and its alloys into nanostructured aluminum hydroxide, which allows obtaining ceramics with high properties. The heat treatment regime of the original aluminum hydroxide in air (1350  0 C, 1 hour) was developed to convert it into aluminum oxide  (γ  and  α  -  modifications),  ensuring  the  preservation  of  high  activity  of  the aluminum oxide powder for heating and bonding.